1988
DOI: 10.1002/j.1556-6676.1988.tb02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal Versus Vocational Focus in Career Counseling: A Retrospective Outcome Study

Abstract: In this archival study the authors sought to determine the relationship, if any, between counseling outcomes and the topical focus in career counseling. Twenty-two counselors saw 46 adult clients at a community-based clinic for an average of eight sessions. Counseling outcome and topical focus (the extent to which the actual content of counseling sessions reflected relatively more vocationally or personally focused topics) were assessed from follow-up questionnaires to former career clients and from trained ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…Eighty-five percent reported that they had already taken actions such as pursuing courses and degrees, gathering more information, and changing occupations or jobs; only 15%said that they had done nothing since their last interview. The rate of satisfaction seems to be slightly higher than the rate Phillips et al (1988) found in their I-year follow-up of a small sample of career counseling clients from a community clinic.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Eighty-five percent reported that they had already taken actions such as pursuing courses and degrees, gathering more information, and changing occupations or jobs; only 15%said that they had done nothing since their last interview. The rate of satisfaction seems to be slightly higher than the rate Phillips et al (1988) found in their I-year follow-up of a small sample of career counseling clients from a community clinic.…”
Section: Discussioncontrasting
confidence: 64%
“…Because the ratings of progress and counselor were highly correlated (r = .71, P < .01), they were combined as in Robbins et ai. (1994) and Phillips, Friedlander, Kost, Specterman, and Robbins (1988). The mean was 1.08 (SD= 0.74).…”
Section: Overall Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of clinical assignment, the misjudgment of the "simplicity" of career concerns as compared to "personal" issues (Gelso et al, 1985) may lead to the assignment of vocational clients to less experienced practitioners. Such a practice would be contrary to recommendations derived from studies that support that the expertise of the counselor is a predictor of client satisfaction with career counseling (Phillips et al, 1988).…”
Section: Resultsmentioning
confidence: 68%
“…Career counseling has been designated as the historical foundation and as one of the future directions for college counseling (Benjamin & Walz, 1989;Phillips, Friedlander, Kost, Specterman, & Robbins, 1988;Spengler, Blustein, & Strohmer, 1990). Congruent with the counseling philosophy, theories of career evolution stress a life-span orientation, and integrate themes of education, development, adjustment, and growth (Hackney, 1990;Herr, 1991;Hoyt, 1990).…”
mentioning
confidence: 99%